IMPROVING FINANCIAL STABILITY OF CONSTRUCTION COMPANIES IN THE FINANCIAL CRISIS - , А. И., И. С. (Municipal economy of cities. Series: «Economy science», 2013)
The paper presents the organizational and technical solutions aimed at improving the financial sustainability of the construction companies in the financial crisis. The studies were conducted on the example of a construction company specializing in the construction of residential buildings.